2018
DOI: 10.3389/fphys.2018.00939
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Sulfonate Attenuates Acute Lung Injury by Reducing Expression of Myeloperoxidase and Neutrophil-Derived Proteases in Mice

Abstract: Andrographolide sulfonate (Andro-S), a sulfonation derivative of andrographolide, is known to be effective in treating inflammation-related diseases, while the underlying mechanisms and global protein alterations in response to Andro-S remain unknown. This study aimed to investigate the pharmacological effects and potential targets of Andro-S in a murine model of acute lung injury (ALI). ALI was induced by aerosolized lipopolysaccharide (LPS) exposure before treatment with Andro-S. Inflammatory state of each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Immunohistochemistry (IHC) was also performed using TNF‐α (1:100; Abcam, #ab6671) and IL‐6 (1:200; Abcam, #ab6672) antibodies as described previously …”
Section: Methodsmentioning
confidence: 71%
“…Immunohistochemistry (IHC) was also performed using TNF‐α (1:100; Abcam, #ab6671) and IL‐6 (1:200; Abcam, #ab6672) antibodies as described previously …”
Section: Methodsmentioning
confidence: 71%
“…iTRAQ quantitative proteomic technology has received wide attention since its introduction. This technology is often used in the research of animals with different classification levels (Gao et al, 2018; Jia et al, 2018; Song et al, 2018). However, the use of iTRAQ quantitative proteomics to study these important parasitic organisms—ticks have rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil in ltration and HNE and MPO expression are associated with the progression of ALI [1,30]. To study the effects of PVAP on ALI, BALF and lung tissues of mice were collected, and the protective effects of PVAP were determined by analyzing total protein content and MPO and HNE activities.…”
Section: Pvap Suppresses Hne and Mpo Activities And Inhibits Neutrophmentioning
confidence: 99%
“…Acute lung injury (ALI) and acute respiratory distress syndrome, as common complications of pneumonia, severe sepsis, trauma, and inhalation injury, are cardiopulmonary diseases with high mortality rates [1,2]. No effective therapeutic agents are available for ALI, and supportive care is the typical clinical approach [1,3]; thus, new agents to treat or prevent ALI are needed.…”
Section: Introductionmentioning
confidence: 99%